2020
DOI: 10.1002/cche.10279
|View full text |Cite
|
Sign up to set email alerts
|

Utilization potential of Glutograph in wheat breeding programs and the influence of genotype and environment on bread wheat quality

Abstract: Background and objectives Glutograph is a relatively new instrument to determine the stretch (GS) and relaxation (GR) properties of wheat gluten. The aims of this research were to determine heritability values of GS and GR and to investigate the effects of genotype and environment on some quality parameters and yield. The relationship between Glutograph parameters and other traits was also investigated by using correlation and biplot analyses. Findings Wide ranges of variability values were observed among both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, there is no consensus on the influence of genotype and/or environment on the TW. There are reports in the literature describing genotype effect as predominant (Taghouti et al., 2010), whereas other authors have stated that the location of growing area was dominant (Subira et al., 2014) or similar (Kaplan Evlice et al, 2020). TW values were higher (79.25–89.05) than those found in wheat genotypes grown in different locations in Southern of Brazil (Rio Grande do Sul State), that ranged between 73.75 and 79.83 kg/hl for TBIO Sintonia and CD 1,303 genotypes, respectively (Miranda et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no consensus on the influence of genotype and/or environment on the TW. There are reports in the literature describing genotype effect as predominant (Taghouti et al., 2010), whereas other authors have stated that the location of growing area was dominant (Subira et al., 2014) or similar (Kaplan Evlice et al, 2020). TW values were higher (79.25–89.05) than those found in wheat genotypes grown in different locations in Southern of Brazil (Rio Grande do Sul State), that ranged between 73.75 and 79.83 kg/hl for TBIO Sintonia and CD 1,303 genotypes, respectively (Miranda et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…As gluten strength and quality increase, relaxation value decreases, and stretch (s) value increases. The gluten quality of TDF was lower when compared with the different bread wheat cultivars that belonged to Regional Yield Trials (Central Research Institute for Field Crops, Ankara, Türkiye) [17]. Although TDF had a signi cantly higher amount of gluten and gliadin than TAF (p < 0.05), the gluten quality of TDF was lower than TAF.…”
Section: Quality Parametersmentioning
confidence: 90%
“…According to the Table 1, we found that wheat contain the highest content of carbohydrate. Wheat (61.6-83.1%) [45,46,[54][55][56][57][58][59], Buckwheat (63.1-82.1%) [50-52] [60-62], Rice (71.1-78.2%) [47,48,62] Quinoa (48.5-77.0%) [35,38,60,61], corn (65.0-74.3%) [33,41,42] and amaranth (63.1-70.0%) [34][35][36]50]. Starch is the primary carbohydrate, accounting for 58.1-64.2%, 65.0-75.0%, and 54.5-57.4% of total seed dry weight in quinoa, amaranth, and buckwheat, respectively [62].…”
Section: Carbohydrates and Starch In Pseudo Cereals And Cerealsmentioning
confidence: 99%
“…The protein content and profile of all plants are determined by genotype and growing conditions. Compared to cereals, pseudo cereals offer superior nutritional value, primarily due to their higher protein levels, which vary from 9.1 to 16.7% quinoa [35,38,60], 13.1-21.5% for amaranth [34][35][36]50] and buckwheat 5.7-14.2% [50][51][52][60][61][62] and cereals wheat 8-19.0% [45,46,[54][55][56][57][58][59], rice 6.8-7.3% [47,48,62] and corn 8.8-9.4% [41,42] The major protein fractions found in qunioa grains are 11S-type globulins and 2S albumins, which account for 27.9-60.2% and 13.2-42.3% of total seed proteins, respectively, followed by glutelins (18.1-31.6) and Prolamins comprise a lower protein proportion (0.5-19.3% of total seed protein) [63,64]. Amaranthine, an essential protein found in the globulins portion with a molecular weight of more than 300kDa and three subunits: pro amaranthine, one basic peptide, and one acidic [35].…”
Section: Protein In Pseudo Cereals and Cerealsmentioning
confidence: 99%